INFLUENCE OF HOMEGROWN SCHOOL FEEDING PROGRAMME ON DIETARY DIVERSITY AMONG SCHOOL CHILDREN 6-13 YEARS OF AGE IN MAKUENI COUNTY, KENYA - Kimwele, A. M.; Ochola, S. A; Mugambi, M. N (European Journal of Health Sciences, 2021)
Purpose: The main objective of this study was to establish the difference in the dietary diversity for school children enrolled in and those not enrolled in the home grown school feeding programme (HGSFP), in Makueni County, Kenya. Methodology: A school based cross-sectional study design was used, Makindu sub-County in Makueni County was purposively sampled, and stratified into school with HGSFP and schools without HGSFP. Using G Power 3.1.2, Sample size calculator, 288 school children were sampled, 144 children randomly selected from three schools offering HGSFP and 144 children randomly selected from three schools without HGSFP, translating to 48 school children per school. Further the study sampled six (6) children per class from class one to standard eight using respective daily class attendance registers where the first respondents in each class were selected at random and the subsequent ones systematically. Researcher administered questionnaire was used to collect data from child/caregiver pair. The information collected was analyzed and the results were presented in tables and percentages. Findings: A significant difference was observed in children religion, as more children not in HGSFP were protestants compared to Catholics (p= 0.004). Mothers’ education level, mothers’ occupation and fathers’ education level across the groups were statistically significant, P-value <0.05. The main source of cooking fuel for households with children in the HGSFP was firewood (50.0%) and for children not in the HGSFP preferred firewood (47.9%). All (100%) of the children had consumed staple foods, followed closely by consumption of legumes, nuts and seeds by children in (98.6%) the HGSFP and those not in (75.7%) the programme. Vitamin a rich fruits and vegetables (13.9%, 11.8%), organ meat (1.4%, 4.9%) and eggs (2.8%, 2.1%) were poorly consumed by children in the HGSFP and those not in the programme respectively, these differences in food consumption pattern were statistically significant, p-value <0.05, thus children in HGSFP had better dietary diversity compared to those not in the programme. Conclusion and recommendation: Given the positive outcome that children in the HGSFP had a better diversified diet, the study recommends scaling up the programme in all schools especially in the food insecure areas. In addition, there is need for a longitudinal study which includes all the seasons of the year so as verify the results of this study as well as determine the sustainability of the program for a better policy formulation.
Keywords: Home Grown School Feeding Programme (HGSFP); School children; Dietary diversity